Listening : Interviews, 1970-1989 - Cott, Jonathan (Book collections on Project MUSE., 2020)
"Featuring luminaries such as Chinua Achebe and Lou Reed, from Bob Dylan to Dr. Seuss, from Carl Sagan to Elizabeth Taylor, the conversations in Listening brim with fun cultural trivia, astute psychological observations, and the rare candid look at larger than life personalities. This mosaic is the culmination of a life's work and will be beloved by casual and serious readers alike"--